Indexes and Models to Predict the Occurrence of Forest Fires: A Review for Mexico - González Gutiérrez, Ignacio (2023)
In Mexico, protecting forests and jungles through a set of practices and efforts aims at preventing activities that affect them. These practices are divided into three categories within a fire management framework: cultural prevention, physical prevention, and le- gal protection. Within cultural prevention, studies on indices and probability models of fire occurrences stand out. The objective set forth in this work has been to present the different methodological proposals of indices and models developed in Mexico to predict the occurrence of forest fires, analyzing their methodological approaches and variables used. Digital and printed bibliographic materials from the end of the 20th century to 2018 were searched. Thirty-eight models and indexes were identified. The states of Durango and Mexico stand out with more than three studies each. These results make evident the lack of hazard systems in vast regions of the country.